Progress in diagnosis and treatment of chronic inflammatory demyelinating polyradiculoneuropathy - Bunschoten, Carina; Jacobs, Bart C; Van den Bergh, Peter Y K; Cornblath, David R; van Doorn, Pieter A (Lancet neurology, 2019)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a rare and heterogeneous but treatable immune-mediated neuropathy. Nerve conduction studies are considered essential for a definite diagnosis, but poor performance and misinterpretation of the results frequently leads to misdiagnosis. Nerve ultrasound and MRI could be helpful in diagnosis. Whereas typical CIDP is relatively easy to diagnose, atypical variants with distinct phenotypes can be a diagnostic challenge. Intravenous or subcutaneous immunoglobulin, corticosteroids, and plasma exchange are effective treatments, but maintenance treatments are often required for years, and treatment regimens require careful and regular adjustments to avoid undertreatment or overtreatment. Patients who do not improve, or insufficiently improve after treatment, might have specific characteristics related to a distinct disease mechanism caused by immunoglobulin G4 antibodies to nodal or paranodal proteins, and could require alternative treatments. Future studies should focus on curative and individualised treatment regimens to improve the patient's condition and to prevent further nerve damage.